Upon correlating diameters measured by optical particle counters and aerodynamic particle sizers. (November 2016) - Chien, Chih-Hsiang; Theodore, Alexandros; Wu, Chang-Yu; Hsu, Yu-Mei; Birky, Brian
Abstract: Converting optical diameter measured by an optical particle counter (OPC) to aerodynamic diameter measured by an aerodynamic particle sizer (APS) is of interest because the OPC is more affordable and portable. In this study, optical diameter was compared with volume equivalent diameter derived from aerodynamic diameter using monodisperse oleic acid and sodium chloride test aerosols generated by a Vibrating Orifice Aerosol Generator (VOAG). While prior studies assumed optical diameter to be equal to volume equivalent diameter, experimental results showed the assumption to be valid only if the aerosol has the same optical properties as standard polystyrene (PSL) particles. For oleic acid aerosol, the optical diameter was less than the derived volume equivalent diameter because its refractive index ( m =1.46) is less than of PSL ( m =1.60). While the refractive index of sodium chloride ( m =1.54) is close to that of PSL, a much larger optical diameter of sodium chloride than its volume equivalent diameter was observed due to its irregular crystallography. Regression equations derived from the calibration were verified by testing with a validated respirable sampler. With known refractive index and shape factor, these equations can convert optical diameter directly to aerodynamic diameter with a residual bias less than 1 µm. Highlights: We experimentally calibrated optical diameter with aerodynamic diameter. The optical diameter of oleic acid is smaller than its volume equivalent diameter. The optical diameter of NaCl is much larger than its volume equivalent diameter. Calibration curves were obtained to link optical diameter to aerodynamic diameter.